Global burden and risk factors of type 2 diabetes mellitus from 1990 to 2021, with forecasts to 2050 - Huang, Qian; Li, Yang; Yu, Minggang; Lv, Zhizi; Lu, Fengyi; Xu, Ning; Zhang, Qingqing; Shen, Jiayun; Zhu, Jinfeng; Jiang, Hua (Frontiers in Endocrinology, 2025)
BackgroundType 2 diabetes mellitus (T2DM) presents a substantial strain on global healthcare systems. This study seeks to offer robust scientific evidence for the effective prevention and management of T2DM globally through a comprehensive analysis of the disease’s burden, trends, and risk factors from 1990 to 2021, as well as future trajectories from 2022 to 2050.MethodsData for this study were sourced from the 2021 Global Burden of Disease (GBD) study. T2DM burden was assessed through incidence, prevalence, mortality, and disability-adjusted life years (DALYs), stratified by age, sex, sociodemographic index (SDI), 21 GBD regions, and 204 countries/territories. Trends from 1990 to 2021 were quantified by estimating annual percentage changes. Decomposition analysis identified the primary population-level drivers of T2DM burden changes. The population attributable fraction assessed the contribution of risk factors to the T2DM burden over the past 30 years, while the Bayesian age–period–cohort model was employed to predict the future burden driven by risk factors.ResultsIn 2021, T2DM affected 506.0 million individuals, with 23.9 million new cases, 1.6 million deaths, and 75.3 million DALYs. Between 1990 and 2021, both absolute and relative burdens of T2DM increased, particularly among males, older adults, and individuals under 40. Regions with higher SDI generally exhibited higher age-standardized incidence and prevalence rates, while those with lower SDI had elevated age-standardized mortality and DALY rates. Oceania stood out as an exception, with the highest relative burdens across all four indicators, most notably in the Marshall Islands and Fiji. The increases in incidence, DALYs, and prevalence were predominantly driven by population growth and epidemiological shifts, with aging contributing significantly to the rise in mortality. Elevated fasting plasma glucose, body mass index (BMI), and particulate pollution were major contributors to higher T2DM-related mortality and DALY rates. By 2050, high BMI, alcohol consumption, and sugary beverages are anticipated to increasingly influence the T2DM burden.ConclusionFocused, preventive interventions targeting key risk factors in high-burden groups can effectively reduce the global T2DM burden.